2017
DOI: 10.22214/ijraset.2017.1004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Investigation of Magnesium Matrix Composite with Titanium Oxide by Powder Metallurgy

Abstract: The investigations of magnesium based matrix material reinforced with the TiO 2 particles with various weight ratios of 2.5, 5, 7.5 and 10% are presented in this research paper. The purpose of this work is to elaborate the manufacturing processes of pure magnesium with the addition of Titanium oxide through the powder metallurgy route. The powder blending was done with the energetic ball and jar mill. The compaction pressure of 650Mpa is given to improve cold compaction. The Sintering temperature of 550 o C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A various characteristics of the magnesium could be enhanced by forming alloys and composites through proper selection of alloying elements and particle reinforcements. The after heat treatment process could be further improved these characteristic by forming secondary phases of the elements present in the alloys and composites [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A various characteristics of the magnesium could be enhanced by forming alloys and composites through proper selection of alloying elements and particle reinforcements. The after heat treatment process could be further improved these characteristic by forming secondary phases of the elements present in the alloys and composites [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the Magnesium metal can be enhanced by the alloying/composite elements through heat treatment. The researchers suggested that the inclusion of ceramic particles is in the magnesium matrix could be improved the mechanical characteristics of magnesium alloys/composites [3]. The included/reinforced metal particles in the matrix forming different phases.…”
Section: Introductionmentioning
confidence: 99%
“…In-general, the most of the studies are focusing the Mg composites based on their characteristics improvement through varying the grain size, weight fraction, morphology, reinforcement particles distribution and by altering the composites forming techniques [9][10][11][12]. Recent years, several alloys/composites were developed using titanium oxide (TiO2) as the reinforcement in Mg matrix through powder metallurgy methods [3,13,14]. The incorporation of TiO2 particles improved the strength of the composites than the pure form of Mg metal.…”
Section: Introductionmentioning
confidence: 99%